2009
DOI: 10.1007/s10853-008-3072-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of three-dimensional interconnected alumina/steel metal matrix composites

Abstract: Three-dimensional interconnected alumina/ steel metal matrix composites (MMCs) were produced by pressureless Ti-activated melt infiltration method using three types of Al 2 O 3 powder with different sizes and shapes. By partial sintering during infiltration an interpenetrating ceramic network was realised. The effect of the ceramic particle size and shape on the resulting ceramic network, volume % fraction and the MMC properties is presented. The MMCs were characterised for mechanical properties at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Minor fractions of metastable zirconia particles showing a martensitic phase transformation under loading can further improve the mechanical properties of similar composite materials. Yet, high‐temperature applications of such material combinations have rarely been reported since the TRIP effect is restricted to moderate temperatures …”
Section: Introductionmentioning
confidence: 99%
“…Minor fractions of metastable zirconia particles showing a martensitic phase transformation under loading can further improve the mechanical properties of similar composite materials. Yet, high‐temperature applications of such material combinations have rarely been reported since the TRIP effect is restricted to moderate temperatures …”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the calculated maximum bending strength value of the MMC specimen reaches to 889 MPa, which is much higher than that of the MMCs produced by steel melt infiltrating Ti-activated alumina particles [7,12]. Remaining of porous areas without melts infiltration and transgranular cracking failure of the unconnected ceramic particles result in the lower strength of the MMCs based on ceramic particles [12]. In the case of the present network MMCs, each phase contributes to the final properties.…”
Section: Bending Strengthmentioning
confidence: 99%
“…It can be found that, for the two materials, with the increase of the normal load values, the worn depths of the wear scars gradually increase; whereas friction coefficients appreciably decrease contrarily. However, a relative lower depth value of the wear scar appears in the [7] ≤ 282 Interconnected particles [12] ≤ 605 3-D network skeletons 819 -889 MMCs when the load value is equal, which is corresponding to slight damage compared with the pure steel matrix. Moreover, the pure steel matrixes exhibit larger fluctuations of friction coefficients versus fretting cycles number than the MMCs, demonstrating the latter has better fretting wear stability [13].…”
Section: Fretting Wear Analysesmentioning
confidence: 99%
“…The preparation of this kind ceramic material can be carried out by e.g. by sintering the fractionated grains [10][11][12][13][14], gelling a foamed ceramic suspension [6,8,[15][16][17] or using open-cell polymer foam.…”
Section: Introductionmentioning
confidence: 99%